ANALYSIS OF EFFECT OF AMLA RASA (SOUR FOOD) IN DIFFERENT CONCENTRATIONS ON MAMSA DHATU (MUSCLE TISSUE) - Kumar, *Akshay; Prashanth, Kekuda; Pratibha, Kulkarni; Ravi, M; Sudhakar, Bhat (International Journal of Ayurveda and Pharma Research, 2018)
It is said that one should consume Shad-Rasayuktha Ahara for better nourishment. The nutritive value of the 6 Rasas (taste) has been explained in the classics of Ayurveda along with their harmful effects when used in excess. When Amla Rasa is taken in excess it produces Dantaharsha (Morbid sensation of teeth), Trishna (thirst) etc.Objectives - The present study is designed by administering Amla Rasa Pradhana Drvya given in different concentration 10% and 15% and effect on the Mamsa Dhatu is assessed by certain blood parameters.Material and Methods -Wistar strain albino rats of either sex, weighing of 200-300 g. Obtained from S.D.M Centre for Research in Ayurveda, Udupi, Karnataka. 5Groups were taken and Group 1 is Control, Group-2 is 15% Chincha, Group-3 is 15% Vrukshamla, Group-4 is 10% Chincha, Group-5 is 10% Vrukshamla which receives drug and laboratory food for 28days, next day blood was collected by supra-orbital puncture with the help of micro capillary tubes under mild ether anesthesia.Results - There was increase in the Total Protein, Serum Albumin and serum creatinine levels and decrease in Serum globulin, Serum Urea level and Body weight.Conclusion – the study suggests that there is catabolic action of the Amla Rasa on the Mamsa Dhatu and anabolic act action on serum protein especially at the level of liver, so there will be a loss of muscle tissue which suggests Mamsa Vidhahyati action.